Enhancing English Proficiency Through Vlog Assignments: A Case Study of Information Systems Students’ - Amalia Solikhah, Nur; Galuhwardani, Cindyra; Rejeki, Sri; Sari, Angela Bayu Pertama (CV. Tripe Konsultan, 2025)
This study evaluated whether assigning student-created video blogs (vlogs) could improve English language proficiency and engagement in an Information Systems ESP course. Thirty undergraduate Information Systems students completed a series of individual and group vlog projects on technical topics (e.g. “Introduction to Information Systems”). Data were collected via standardized pre- and post-speaking tests, semi-structured interviews, and a student survey at the end of the semester. Speaking test scores improved substantially (mean gain ≈ 47.5%), with notable advances in fluency, pronunciation, and use of domain-specific vocabulary. Qualitative feedback indicated high student interest and satisfaction: most students reported increased confidence in speaking and active engagement with course content. These results suggest that integrating vlog assignments in a technical ESP context can strengthen both general English skills and subject-matter communication. Practical implications and limitations are discussed, and directions for future research are proposed.